(untitled) (Research, Society and Development, 2021)
Low pasture production is due to degradation that leads to soil erosion processes. These conditions decrease the production of forage biomass and its resistance to drought. Thus, this study aimed to evaluate the viability of U. decumbens and millet consortium and in single cultivation, related to bromatological quality, using biological activator. The study was carried out in the field located in the experimental area of the Universidade Estadual de Mato Grosso do Sul - Unidade Universitária de Aquidauana (UEMS / UUA), phytotechnics sector, located in the city of Aquidauana MS, region of the Pantanal ecotone. It was adopted a randomized blocks in subdivided plots experimental design with 4 replications, treatments classified in: T1: Millet + activator, T2: Millet, T3: 75% Millet and 25% U. decumbens + activator, T4: 75% Millet and 25% U. decumbens, T5: U. decumbens + activator, T6: U. decumbens, T7: 25% Millet and 75% U. decumbens + activator, T8: 25% Millet and 75% U. decumbens, T9: 50% Millet and 50% U. decumbens + activator, T10: 50% Millet and 50% U. decumbens. At 70 DAE samples consisting of 60 leaves per plot were collected in each treatment. The collected part was the flag leaf, eliminating the basal third portion, apical and the midrib of each leaf. Then the analyzes of dry matter, ashes, PB, FDN and FDA were performed. The treatments that presented the best nutritional values were T3 and T4, however, analyzing grazing efficiency, it is recommended the treatments T7 and T8, once that they showed similar quality and they would be better used by the animals.